HUBUNGAN ANTARA DASAR-DASAR SEGMENTASI DENGAN KEPUTUSAN PEMBELIAN MEREK AIR MINUM KEMASAN GALON - Isnaini Asiati, Diah; Tetuka, Jaka (Universitas muhammadiyah palembang, 2013)
Problem formulation in this research are there relationship between the fundamentals of segmentation with the purchase decesion gallon water in Palembang. The purpse of this study to identify and analyze the relationship between the fundamentalas of segmentation with the purchase decesion gallon water in Palembang. This research is the associative study. The variables of this study are the basic segmentation and purchasing decision. The data used in this research isthe primary data. Data collection method is questionnaire. Analysis of the data used is Chi Square. Based on research done then it canbe inferred that there is a significant relationship between the fundamentals of segmentation with the purchase decision gallon water in Palembang. In conjunction with the basics that segmentation is significant relationships between proven segmentation demographicand purchase decision, as well as between segmentation psicographic and purchase decesion